LGI1 antibody encephalopathy overlapping with sporadic Creutzfeldt-Jakob disease. Issue 4 (August 2016) - Kim, Boaz; Yoo, Patrick; Sutherland, Tom; Boyd, Alison; Stehmann, Christiane; McLean, Catriona; Collins, Steven
Abstract : Objective: To report a rare case of leucine-rich, glioma inactivated 1 (LGI1) antibody–mediated autoimmune encephalopathy clinically overlapping with pathologically confirmed sporadic Creutzfeldt-Jakob disease (CJD). Methods: The patient was investigated with repeated brain MRI, EEG, CSF examination, whole-body fluorodeoxy-glucose positron emission tomography, genetic analysis of the prion protein gene ( PRNP ), and extensive serologic screening for paraneoplastic and autoimmune encephalopathy markers. Written informed consent was obtained from the patient's next of kin for access to clinical files for research purposes and for publication. Results: The patient was a 77-year-old man who presented with faciobrachial dystonic seizures (FBDS) secondary to LGI1 antibody–mediated autoimmune encephalopathy, with suggestive MRI findings and a complete response to treatment with combinatorial immunosuppression. Stereotactic biopsy of a nonenhancing T1 hyperintense basal ganglia lesion during the initial FBDS phase, albeit following immunosuppression, did not disclose evidence of lymphocytic inflammation. Following full remission of the FBDS, the patient manifested a rapidly progressive dementia associated with gross motor decline confirmed to be CJD at autopsy (molecular subtype VV3), with no evidence of a pathogenic PRNP mutation. Conclusions: Our patient highlights that these rare diseases are not invariably mutually exclusive and underscores the benefits of comprehensive neuropathologic examination of the brain to achieve an accurate diagnosis, especially in complex cases when the clinical trajectory dramatically deviates and a concomitant disease may need to be conscientiously considered to best explain the new clinical course.